(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
Ergative verbs (also known as labile or ambitransitive verbs) in English allow the same noun phrase to function as the direct object in transitive constructions and as the subject in intransitive ones, typically conveying processes of change of state, position, or movement without explicitly mentioning an external agent in the intransitive form. This paper examines the semantic features of ergative verbs—emphasizing patient-focus, agent-defocusing, and causation—and analyzes their realization in selected short stories by O. Henry, including "The Gift of the Magi," "The Last Leaf," and "The Ransom of Red Chief." Through qualitative textual analysis, the study demonstrates how O. Henry employs ergative constructions to create narrative ambiguity, irony, and stylistic economy, enhancing thematic elements of fate, transformation, and human agency. The findings highlight the role of ergative verbs in literary discourse, contributing to stylistics and transitivity studies in English fiction.